Understanding therapy-related AML: genetic insights and emerging strategies for high-risk patients - Jerez, Joaquín; Hernandez, Caterina; Hill, Charlotte N. (Frontiers in Hematology, 2025)
Therapy-related acute myeloid leukemia (t-AML) is a complex clinical entity characterized by its association with prior exposure to cytotoxic agents or radiotherapy. Recent analyses have unveiled the intricate molecular landscape of t-AML, revealing a heterogeneous genetic profile marked by mutations in TP53, PPM1D, and other genes. While t-AML does not constitute a distinct molecular entity, its prognostic impact is integrated into current risk classifications, with particular emphasis on TP53 mutations. Treatment strategies should be guided by the underlying biology of the disease rather than solely by clinical history. The significance of t-AML lies in its role as a qualifying condition rather than an independent disease entity. Its association with germline mutations and clonal hematopoiesis of indeterminate potential represents an emerging and promising field for developing preventive and monitoring strategies. The standard therapeutic approach for t-AML has evolved, with promising alternatives emerging. The CPX-351 regimen has demonstrated superior outcomes compared to conventional 3 + 7 induction therapy in selected patients. The incorporation of Venetoclax, both in combination with hypomethylating agents and in high- or low-intensity chemotherapy regimens, has shown efficacy in high-risk AML, including t-AML cases; however, its validity must be confirmed in prospective studies. Allogeneic hematopoietic stem cell transplantation remains a crucial consolidation strategy. Participation in clinical trials is of paramount importance to optimize management strategies for this high-risk AML subset.